Endogenous LRRK2 and PINK1 function in a convergent neuroprotective ciliogenesis pathway in the brain - Enrico Bagnoli; Yu-En Lin; Sophie Burel; Ebsy Jaimon; Odetta Antico; Christos Themistokleous; Jonas M. Nikoloff; Samuel Squires; Ilaria Morella; Jens O. Watzlawik; Fabienne C. Fiesel; Wolfdieter Springer; et al. (Proceedings of the National Academy of Sciences, 2025)
Mutations in Leucine-rich repeat kinase 2 (LRRK2) and PTEN-induced kinase 1 (PINK1) are associated with familial Parkinson’s disease (PD). LRRK2 phosphorylates Rab guanosine triphosphatase (GTPases) within the Switch II domain while PINK1 directly phosphorylates Parkin and ubiquitin (Ub) and indirectly induces phosphorylation of a subset of Rab GTPases. Herein we have crossed LRRK2 [R1441C] mutant knock-in mice with PINK1 knock-out (KO) mice and report that loss of PINK1 does not impact endogenous LRRK2-mediated Rab phosphorylation nor do we see significant effect of mutant LRRK2 on PINK1-mediated Rab and Ub phosphorylation. In addition, we observe that a pool of the Rab-specific, protein phosphatase family member 1H phosphatase, is transcriptionally up-regulated and recruited to damaged mitochondria, independent of PINK1 or LRRK2 activity. Parallel signaling of LRRK2 and PINK1 pathways is supported by assessment of motor behavioral studies that show no evidence of genetic interaction in crossed mouse lines. Previously we showed loss of cilia in LRRK2 R1441C mice and herein we show that PINK1 KO mice exhibit a ciliogenesis defect in striatal cholinergic interneurons and astrocytes that interferes with Hedgehog induction of glial derived-neurotrophic factor transcription. This is not exacerbated in double-mutant LRRK2 and PINK1 mice. Overall, our analysis indicates that LRRK2 activation and/or loss of PINK1 function along parallel pathways to impair ciliogenesis, suggesting a convergent mechanism toward PD. Our data suggest that reversal of defects downstream of ciliogenesis offers a common therapeutic strategy for LRRK2 or PINK1 PD patients, whereas LRRK2 inhibitors that are currently in clinical trials are unlikely to benefit PINK1 PD patients.